2020
DOI: 10.1111/all.14288
|View full text |Cite
|
Sign up to set email alerts
|

CD23 expression on switched memory B cells bridges T‐B cell interaction in allergic rhinitis

Abstract: Background: The contribution of B-cell subsets and T-B cell interaction to the pathogenesis of allergic rhinitis (AR) and mechanisms of allergen immunotherapy (AIT) remain poorly understood. This study aimed to outline circulating B-cell signature, the underlying mechanism, and its association with clinical response to AIT in patients with AR. Methods: IgD/CD27 and CD24/CD38 core gating systems were used to determine frequencies and phenotypes of B cells. Correlations between B cells, T cells, antigenspecific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 51 publications
1
51
0
Order By: Relevance
“…These cells were able to restrain class switching to IgE, but not IgG, via IL‐10 in vitro 86 . In addition, cT FR cells derived from patients with AR had a compromised IL‐10‐producing capacity relative to those obtained from healthy subjects 87 …”
Section: Tfh and Tfr Cells In Allergic Diseasesmentioning
confidence: 98%
See 3 more Smart Citations
“…These cells were able to restrain class switching to IgE, but not IgG, via IL‐10 in vitro 86 . In addition, cT FR cells derived from patients with AR had a compromised IL‐10‐producing capacity relative to those obtained from healthy subjects 87 …”
Section: Tfh and Tfr Cells In Allergic Diseasesmentioning
confidence: 98%
“…Using unsupervised hierarchical clustering and correlation analysis, additional negative correlations have been identified in the cT FR cell frequencies, with symptom scores and allergen‐specific IgE levels in patients with AR 35,87 . Notably, cT FR /cT FH 2 cell ratios show a better correlation with symptom severity than the frequencies of T FR cells ( r = −.516 for cT FR /cT FH 2 cell ratio vs r = −.427 for T FR cells), 35,87 emphasizing the importance of T FH and T FR cell balances in the pathogenesis of AR.…”
Section: Tfh and Tfr Cells In Allergic Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that the expression of CD23 was enhanced on CD19 + CD20 + CD27 + IgD − switching memory B cells and positively correlated with antigen‐specific IgE levels and the T FH 2 cell ratio in AR patients. T FH 2 cells have the capacity to promote CD23 expression on switching memory B cells by secreting the cytokine IL‐4 122 …”
Section: Tfh Cells In Immune‐associated Diseasesmentioning
confidence: 99%